A qualitative review of misinformation and conspiracy theories in skin cancer. (1st October 2022) - O'Connor, Cathal; Rafferty, Siobhán; Murphy, Michelle
Abstract: Misinformation on diseases and treatments is a worldwide threat and can lead to worse outcomes for patients with skin cancer. The aim of this study was to qualitatively assess the content of online misinformation related to skin cancer. Searches were performed via PubMed and Google using the terms 'skin cancer' OR 'melanoma' OR 'non‐melanoma skin cancer' OR 'SCC' OR 'BCC' AND 'misinformation' OR 'disinformation' OR 'conspiracy theories'. The most common themes of misinformation related to skin cancer included assertions of the 'dangers' of using sunscreen and alternative sunscreen practices; promotion of tanning and Melanotan (an unlicensed and untested form of α‐melanocyte‐stimulating hormone) as safe practices; claims that risk of skin cancer are limited to people who are older or have fair skin; and assertions of alternative 'causes' and alternative 'cures' for skin cancer. Sunscreen was particularly vilified as being an ineffective prophylactic measure and a cause of skin cancer. Dermatologists should be aware of misinformation available online relating to skin cancer, and refute and rebut misleading health information. Abstract : Misinformation on diseases and treatments is a worldwide threat and can lead to worse outcomes for patients with skin cancer. The aim of this study was to qualitatively assess the content of online misinformation related to skin cancer. The most common themes of misinformation related to skin cancer included the 'dangers' of using sunscreen and description of alternative sunscreen practices; tanning as a safe practice; claims that risk of skin cancer is limited to people who are older or have fair skin; alternative 'causes' of skin cancer; and alternative 'cures' for skin cancer.